Artificial leather and method for producing the same
Patent Information
- Application Number
- JP2026520374
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2026-10-16
Smart Images

Figure 2026534548000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to artificial leather and a method for preparing the same.
[0002] Introduction Polyolefin elastomer (POE, including olefin block copolymer (OBC), random POE, etc.) based artificial leather is considered to be an environmentally friendly and sustainable artificial leather product. Compared with current polyvinyl chloride (PVC) leather, POE-based leather contains no halogen and no phthalate plasticizers. Compared with other existing polyurethane (PU) leathers, no solvents (e.g., harmful DMF) are required during the POE-based leather manufacturing process. Therefore, POE leather production is more earth-friendly and minimizes water / air / soil pollution. Although PUD and solvent-free PU are becoming widely used, POE leather still has the advantage of easy recyclability due to its thermoplastic nature. From a performance perspective, POE has excellent weather resistance and low-temperature flexibility, and has no hydrolysis and yellowing problems. In addition, POE leather can more easily meet the lightweight trend in luggage / bags, footwear, and automotive applications, as the density of POE is much lower than that of PVC (about 40%) and PU (about 25%). POE-based leather is considered to be a promising product to replace PVC and PU leather in several applications. However, it remains challenging to develop POE-based artificial leather with improved surface grain retention after embossing while providing acceptable flexibility.
[0003] Accordingly, there remains a certain demand for artificial leather that has improved surface grain retention after embossing while providing acceptable flexibility.
[0004] After sustained investigation, the inventors surprisingly found that soft OBC, or a blend of a certain amount of soft OBC and soft random POE, significantly improved surface texture retention after embossing, while providing similar or even greater flexibility compared to unused or unblended random POE. [Overview of the Initiative]
[0005] In a first aspect of the present disclosure, the present disclosure provides artificial leather having a multilayer structure, wherein the multilayer structure comprises an upper skin layer and a lower fabric layer, and the upper skin layer comprises at least 10% by weight of an olefin block copolymer based on the total weight of the upper skin layer.
[0006] In a second aspect of the present disclosure, the present disclosure provides a method for preparing a multilayer artificial leather, the method comprising preparing an upper skin layer and a lower fabric layer, wherein the upper skin layer comprises at least 10% by weight of an olefin block copolymer based on the total weight of the upper skin layer, and laminating the upper skin layer and the lower fabric layer together. [Brief explanation of the drawing]
[0007] [Figure 1] This shows a photograph of an embossed leather surface. [Modes for carrying out the invention]
[0008] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in which the present invention pertains. Furthermore, all publications, patent applications, patents, and other references referenced herein are incorporated by reference.
[0009] Numerical ranges disclosed herein include all values from the lower limit to the upper limit (including the lower and upper limits). Ranges containing explicit values (e.g., 1 or 2, or 3 to 5, or 6 or 7) include any subrange between any two explicit values (e.g., 1 to 2, 2 to 6, 5 to 7, 3 to 7, 5 to 6, etc.). Unless otherwise stated, implied in the context, or customary in the art, all parts and percentages are based on weight, and all test methods are current as of the filing date of this disclosure.
[0010] Where disclosed herein, the terms “composition,” “formulation,” or “mixture” refer to a physical blend of different components obtained by simply mixing different components by physical means. The sum of the weight percentages of each component in a composition is 100% by weight based on the total weight of the composition.
[0011] In this specification, “and / or” means “and, or alternatively.” All scopes include endpoints unless otherwise indicated.
[0012] As used herein, the term “polymer” refers to a polymer compound prepared by polymerizing multiple monomers, whether of the same or different types. Thus, the general term polymer includes the terms homopolymer (used to refer to a polymer prepared from only one type of monomer, with the understanding that trace amounts of impurities may be incorporated into the polymer structure) and interpolymer, as defined below. Trace amounts of impurities, such as catalyst residues, may be incorporated into and / or within the polymer. Typically, polymers are stabilized with one or more stabilizers in very small amounts ("ppm (parts per million)") of them.
[0013] As used herein, the term “interpolymer” refers to a polymer prepared by the polymerization of at least two different types of monomers. Thus, the term interpolymer includes the term copolymer (used to refer to a polymer prepared from two different types of monomers) and polymers prepared from three or more different types of monomers.
[0014] "Substantially contained" means that the content of a substance is less than 1% by weight, less than 0.5% by weight, less than 0.2% by weight, less than 0.1% by weight, less than 100 ppm, or 0% by weight, based on the total weight of the corresponding composition or layer (e.g., upper skin layer or intermediate foam layer) containing the stated substance.
[0015] This disclosure provides artificial leather comprising a multilayer structure including an upper skin layer and a lower fabric layer, wherein the upper skin layer comprises at least 10% by weight of an olefin block copolymer based on the total weight of the upper skin layer.
[0016] Preferably, the upper skin layer is not foamed.
[0017] Preferably, the lower fabric layer contains a flexible polymer material.
[0018] Preferably, the multilayer structure further includes a foam layer between the upper skin layer and the lower fabric layer.
[0019] Preferably, the upper skin layer is substantially free of propylene / α-olefin copolymer.
[0020] Upper skin layer The upper skin layer contains at least 10% by weight, preferably at least 20% by weight, preferably at least 30% by weight, at least 40% by weight, at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or 100% by weight of an olefin block copolymer, based on the total weight of the upper skin layer. It may also contain ethylene / α-olefin random copolymer in amounts of 90% by weight or less, 80% by weight or less, 70% by weight or less, 60% by weight or less, 50% by weight or less, 40% by weight or less, 30% by weight or less, 20% by weight or less, 10% by weight or less, or 0% by weight. The upper skin layer may also contain one or more optional additives such as processing aids, fillers, blocking agents, pigments and / or dyes, antioxidants, UV stabilizers and / or absorbers, oils, flame retardants, and fillers (such as talc and calcium carbonate).
[0021] Preferably, the upper skin layer is substantially free of propylene / α-olefin copolymer.
[0022] Foam layer The foam layer (also called the intermediate foam layer) comprises at least one of (i) an olefin block copolymer and (ii) an ethylene / α-olefin random copolymer. The foam layer may also contain gases from decomposed blowing agents, or gases from decomposed blowing agents, which have already been partially or completely replaced by air and any unreacted residual blowing agents. The intermediate foam layer may also contain one or more optional additives such as processing aids, fillers, blocking agents, pigments and / or dyes, antioxidants, UV stabilizers and / or absorbers, oils, flame retardants, and fillers (such as talc and calcium carbonate).
[0023] The intermediate foam layer may be compositionally identical to the upper skin layer, except for gases and by-products resulting from the foaming process.
[0024] The intermediate foam layer typically comprises at least 10, or at least 20, more typically at least 40, more typically at least 50, even more typically at least 60 weight percent (wt%) of an olefin block copolymer. The maximum amount of the olefin block copolymer in the intermediate foam layer, based on the total weight of the foam layer, typically does not exceed 90 wt%, more typically does not exceed 80 wt%, and even more typically does not exceed 70 wt%.
[0025] Preferably, the intermediate foam layer is substantially free of propylene / α-olefin copolymer.
[0026] In general, the blowing agent is incorporated into the copolymer composition to be foamed in an amount ranging from 0.1 to 30 phr, preferably 1 to 20 phr, more preferably 2 to 10 phr. The blowing agent is typically incorporated into the molten stream under a pressure sufficient to inhibit its activation, that is, under a pressure sufficient to inhibit foaming of the molten stream during incorporation of the blowing agent and subsequent processing of the composition until the stream is ready to foam.
[0027] When present, the total amount of optional additives present in the foam layer is typically greater than 0 phr, more typically at least 1 phr, and even more typically at least 2 phr. When present, the total amount of optional additives in the foam layer typically does not exceed 10 phr, more typically does not exceed 7 phr, and even more typically does not exceed 5 phr.
[0028] When present, the total amount of optional filler present in the foam layer is typically greater than 0, more typically at least 5, even more typically at least 10 weight percent (wt%). When present, the total amount of optional filler in the foam layer typically does not exceed 60 wt%, more typically does not exceed 40 wt%, and even more typically does not exceed 20 wt%.
[0029] The foam layer is typically prepared by blending or compounding the individual components together in any conventional mixing apparatus, e.g., a Banbury kneader, a Brabender mixer, or any suitable extruder, under conditions and for a period of time that produce at least a substantially homogeneous mixture; calendering the mixture using conventional apparatus and conditions to form a sheet; and then thermal laminating the sheet onto the upper skin layer and / or lower fabric layer using conventional laminating apparatus and conditions. The foam layer is typically not subjected to foaming conditions until it is laminated onto at least one of the upper skin layer or the lower fabric layer, preferably both layers (in the case of a structure of three or more layers). The foaming conditions are such that very fine and regular bubbles are formed throughout the layer. Typical foaming conditions include an oven temperature of 220°C or higher and an oven residence time of 100–120 seconds. The foaming expansion ratio is typically 1.5–4, more typically 2–3, based on the ratio of the thickness after expansion to the original (unexpanded) thickness (referred to herein as the thickness ratio).
[0030] Lower Fabric Layer The lower fabric layer comprises a flexible polymer material which may be woven, nonwoven, knitted, plain knitted, or spunbonded, and may include natural and / or synthetic fibers. In one embodiment, the fabric layer has a density of 100-500, more typically 150-400, and even more typically 200-350 grams / square meter (g / m²). 2 The material is a nonwoven polymer spunbond material weighing ) . Fabrics that can be used in the implementation of this disclosure include, but are not limited to, cotton, silk, and various synthetic materials such as polyolefins (e.g., polyethylene, polypropylene, etc.), nylon, polyester, and polyurethane (e.g., spandex materials). In one embodiment, a preferred fabric is prepared from polyester, polyethylene, or polypropylene. The fabric may or may not undergo pre-lamination treatments such as corona surface treatment and impregnation, and a foam or upper skin layer is finally thermally laminated thereto.
[0031] Ethylene / α-olefin multiblock interpolymer As used herein, the term "ethylene / α-olefin multiblock interpolymer," also known as "ethylene / α-olefin multiblock interpolymer" or "olefin block copolymer (OBC)," refers to an interpolymer comprising ethylene and one or more copolymerizable α-olefin comonomers in polymerized form, characterized by multiple blocks or segments of two or more (preferably three or more) polymerized monomer units, where these blocks or segments differ in terms of chemical or physical properties. Specifically, the term refers to a polymer comprising two or more (preferably three or more) chemically distinct regions or segments ("blocks") linked in a linear manner, i.e., a polymer comprising chemically distinct units that are end-to-end linked (covalently bonded) with respect to the polymerized functional groups, rather than in a pendant or grafted manner. Blocks differ in terms of the amount or type of comonomers incorporated therein, density, amount and type of crystallinity (e.g., polyethylene vs. polypropylene), crystallite size resulting from polymers of such composition, type or degree of stereoregularity (isotactic or syndiotactic), regional regularity or regional irregularity, amount of branching including long-chain branching or hyperbranching, uniformity, and / or any other chemical or physical properties. Block copolymers are characterized by unique distributions of both polymer polydispersity (PDI or Mw / Mn) and block length distribution, for example, based on the effect of using a shuttling agent in combination with a catalytic system. Non-limiting examples of olefin block copolymers of this disclosure and processes for preparing them are disclosed in U.S. Patents 7,858,706(B2), 8,198,374(B2), 8,318,864(B2), 8,609,779(B2), 8,710,143(B2), 8,785,551(B2), and 9,243,090(B2), as well as U.S. Patent Application Publication 20230058913, all of which are incorporated herein by reference in their entirety.
[0032] Ethylene / α-olefin multiblock interpolymers are characterized by multiple blocks or segments of two or more polymerized monomer units that differ in terms of chemical or physical properties.
[0033] In some embodiments, the multiblock copolymer is given by the following formula: (AB) n It can be expressed as follows, where n is at least 1, preferably an integer greater than 1, for example, 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more. Here, "A" represents a hard block or segment, and "B" represents a soft block or segment. Preferably, the A and B segments are linked in a substantially linear manner, as opposed to a substantially branched or substantially star-shaped manner. In other embodiments, the A and B segments are randomly distributed along the polymer chain. In other words, for example, a block copolymer does not typically have a structure such as: AAA-AA-BBB-BB. In other embodiments, the block copolymer does not typically have a third type of block or segment containing different comonomers. In yet another embodiment, each of block A and block B has monomers or comonomers that are substantially randomly distributed within the block. In other words, neither Block A nor Block B contains two or more subsegments (or subblocks) of a distinct composition, such as a tip segment, which has a substantially different composition from the rest of the block.
[0034] Olefin block copolymers are generally produced by chain shuttle methods, such as those described in U.S. Patent No. 7,858,706, which is incorporated herein by reference. Some chain shuttles and related information are described in column 16, lines 39 to 19, line 44. Some catalysts are described in column 19, lines 45 to 46, line 19, and some co-catalysts are described in column 46, lines 20 to 51, line 28. Some method features are described in column 51, lines 29 to 54, line 56. See also U.S. Patents No. 7,608,668, 7,893,166, and 7,947,793, and U.S. Patent Application Publication 2010 / 0197880. See also U.S. Patent No. 9,243,173.
[0035] Preferably, ethylene constitutes the majority mole fraction of the total ethylene / α-olefin multiblock copolymer. That is, ethylene constitutes at least 40% by weight of the total ethylene / α-olefin multiblock copolymer. More preferably, ethylene constitutes at least 50% by weight, at least 60% by weight, at least 70% by weight, or at least 80% by weight, and the substantial remainder of the total ethylene / α-olefin multiblock interpolymer comprises C4-C8 α-olefin comonomers, which may be selected from butene, pentene, hexene, heptane, and octene, preferably 1-butene, 1-hexene, and 1-octene. In one embodiment, the ethylene / α-olefin multiblock interpolymer contains 40% by weight, 50% by weight, or 60% by weight, or 65% to 80% by weight, or 85% by weight, or 90% by weight of ethylene. For many ethylene / octene multiblock interpolymers, the composition contains an ethylene content of more than 80% by weight of the total ethylene / octene multiblock interpolymer, and an octene content of 10% to 15% by weight, or 15% to 20% by weight of the total ethylene / octene multiblock interpolymer.
[0036] Ethylene / α-olefin multiblock copolymers contain varying amounts of “hard” and “soft” segments. A “hard” segment is a block of polymerization units in which ethylene is present in an amount of more than 90% by weight, or 95% by weight, or more than 95% by weight, or more than 98% by weight, up to a maximum of 100% by weight, based on the weight of the polymer. In other words, the comonomer content (content of monomers other than ethylene) in a hard segment is less than 10% by weight, or 5% by weight, or less than 5% by weight, or less than 2% by weight, based on the weight of the polymer, and can be as low as zero. In some embodiments, a hard segment contains all or substantially all units derived from ethylene. A “soft” segment is a block of polymerization units in which the comonomer content (content of monomers other than ethylene) is more than 5% by weight, or more than 8% by weight, or more than 10% by weight, or more than 15% by weight, based on the weight of the polymer. In one embodiment, the comonomer content of the soft segment is more than 20% by weight, or more than 25% by weight, or more than 30% by weight, or more than 35% by weight, or more than 40% by weight, or more than 45% by weight, or more than 50% by weight, or more than 60% by weight, and may be up to 100% by weight.
[0037] Soft segments may be present in the ethylene / α-olefin multiblock interpolymer in amounts of 1% by weight, or 5% by weight, or 10% by weight, or 15% by weight, or 20% by weight, or 25% by weight, or 30% by weight, or 35% by weight, or 40% by weight, or 45% to 55% by weight, or 60% by weight, or 65% by weight, or 70% by weight, or 75% by weight, or 80% by weight, or 85% by weight, or 90% by weight, or 95% by weight, or 99% by weight, of the total weight of the ethylene / α-olefin multiblock interpolymer. Conversely, hard segments may be present in a similar range. The weight percentages of soft segments and hard segments can be calculated based on data obtained from DSC or NMR. Such methods and calculations are disclosed, for example, in U.S. Patent No. 7,608,668, the entirety of which is incorporated herein by reference. In particular, the weight percentages of hard and soft segments and the comonomer content may be determined as described in columns 57 to 63 of U.S. Patent No. 7,608,668.
[0038] In one embodiment, the ethylene / α-olefin multiblock copolymer is produced in a continuous process and has a polydispersity index (Mw / Mn) of 1.7–3.5, or 1.8–3, or 1.8–2.5, or 1.8–2.2. When produced in a batch or semi-batch process, the ethylene / α-olefin multiblock copolymer has an Mw / Mn of 1.0–3.5, or 1.3–3, or 1.4–2.5, or 1.4–2.
[0039] A non-limiting example of suitable ethylene / α-olefin multiblock copolymers is disclosed in U.S. Patent No. 7,608,668, the entire contents of which are incorporated herein by reference.
[0040] In one embodiment, the ethylene / α-olefin multiblock copolymer consists only of (i) ethylene monomer and (ii) C4-C8 α-olefin comonomer.
[0041] In one embodiment, an ethylene / α-olefin multiblock copolymer is defined as having hard segments and soft segments, being styrene-free, consisting only of (i) ethylene and (ii) C4-C8 α-olefins, and having an Mw / Mn ratio of 1.7 to 3.5.
[0042] In one embodiment, the ethylene / α-olefin multiblock interpolymer has a density of about 0.850 g / cc to about 0.890 g / cc, preferably about 0.855 g / cc to 0.880 g / cc, more preferably about 0.858 g / cc to about 0.870 g / cc, and even more preferably about 0.860 g / cc to about 0.866 g / cc.
[0043] Preferably, the ethylene / α-olefin multiblock interpolymer used in this disclosure has an MI of about 30 g / 10 min or less at 190°C / 2.16 kg, preferably about 20 g / 10 min or less at 190°C / 2.16 kg, preferably about 18 g / 10 min or less at 190°C / 2.16 kg, more preferably about 17 g / 10 min or less at 190°C / 2.16 kg, more preferably about 16 g / 10 min or less at 190°C / 2.16 kg, even more preferably about 15 g / 10 min or less at 190°C / 2.16 kg, or 12 g / 10 min or less at 190°C / 2.16 kg. Alternatively, the ethylene / α-olefin multiblock interpolymer used in this disclosure has an MI of about 0.1 g / 10 min to about 20 g / 10 min at 190°C / 2.16 kg, preferably about 0.5 g / 10 min to about 18 g / 10 min at 190°C / 2.16 kg, more preferably about 1 g / 10 min to about 16 g / 10 min at 190°C / 2.16 kg, and even more preferably about 5 g / 10 min to about 15 g / 10 min at 190°C / 2.16 kg.
[0044] Preferably, the ethylene / α-olefin multiblock interpolymer used in this disclosure has a melting point of 100 to 130°C, more preferably 105 to 125°C, and more preferably 110 to 120°C.
[0045] Suitable ethylene / α-olefin multiblock interpolymers may be INFUSE® products from Dow, such as INFUSE® 9107, INFUSE® 9500, INFUSE® 9507, INFUSE® 9807, or OBC1 prepared according to IE6 of U.S. Patent Application Publication No. 20230058913.
[0046] Ethylene / α-olefin random copolymer Ethylene / α-olefin random copolymer (also called random POE) is ethylene / propylene random copolymer or ethylene / C4-C8α-olefin random copolymer. In one embodiment, the ethylene / α-olefin copolymer is ethylene / C4-C8α-olefin copolymer. The ethylene / C4-C8α-olefin copolymer is composed of ethylene in its polymerized form and one copolymerizable C4-C8α-olefin comonomer, or otherwise consists of them. The C4-C8α-olefin comonomer may be selected from butene, pentene, hexene, heptane, and octene, preferably 1-butene, 1-hexene, and 1-octene.
[0047] In one embodiment, the ethylene / α-olefin random copolymer used in this disclosure has a density of about 0.850 g / cc to about 0.900 g / cc, preferably about 0.855 g / cc to 0.895 g / cc, more preferably about 0.857 g / cc to about 0.890 g / cc, and even more preferably about 0.865 g / cc to about 0.885 g / cc.
[0048] Preferably, the ethylene / α-olefin random copolymer used in this disclosure has an MI of about 20 g / 10 min or less (at 190°C / 2.16 kg), preferably about 15 g / 10 min or less at 190°C / 2.16 kg, more preferably about 10 g / 10 min or less at 190°C / 2.16 kg, more preferably about 8 g / 10 min or less at 190°C / 2.16 kg, even more preferably about 7 g / 10 min or less at 190°C / 2.16 kg, or 6 g / 10 min or less at 190°C / 2.16 kg, or 5 g / 10 min or less at 190°C / 2.16 kg. Alternatively, the ethylene / α-olefin random copolymer used in this disclosure has an MI of about 0.1 g / 10 min to about 20 g / 10 min at 190°C / 2.16 kg, preferably about 0.2 g / 10 min to about 15 g / 10 min at 190°C / 2.16 kg, more preferably about 0.3 g / 10 min to about 8 g / 10 min at 190°C / 2.16 kg, and even more preferably about 1 g / 10 min to about 5 g / 10 min at 190°C / 2.16 kg.
[0049] Suitable ethylene / α-olefin random copolymers may be ENGAGE® products from Dow, such as ENGAGE® 8003, ENGAGE® 8842, ENGAGE® 7447, ENGAGE® 8150, ENGAGE® 7467, or OE1 prepared according to Example 1 of U.S. Patent No. 11236241B2.
[0050] foaming agent Almost any known blowing agent (also known as a blowing agent or leavening agent), including gaseous substances, volatile liquids, and chemical agents that decompose into gases and other by-products, can be used. Typical blowing agents include, but are not limited to, nitrogen gas, carbon dioxide gas, air, methyl chloride, ethyl chloride, pentane, isopentane, perfluoromethane, chlorotrifluoromethane, dichlorodifluoromethane, trichlorofluoromethane, perfluoroethane, 1-chloro-1,1-difluoroethane, chloropentafluoroethane, dichlorotetrafluoroethane, trichlorotrifluoroethane, perfluoropropane, chloroheptafluoropropane, dichlorohexafluoropropane, perfluorobutane, chlorononafluorobutane, perfluorocyclobutane, azodicarbonamide (ADCA), azodiisobutyronitrile, benzenesulfonhydrazide, 4,4-oxybenzenesulfonyl semicarbazide, p-toluenesulfonyl semicarbazide, barium azodicarboxylate, N,N'-dimethyl-N,N'-dinitrosotelephthalamide, and trihydrazinotriazine. Currently, ADCA is the preferred blowing agent.
[0051] additives The upper skin layer and intermediate foam layer may contain additives including, but not limited to, antioxidants, curing agents, crosslinking aids, boosters and retarders, processing aids, UV absorbers or stabilizers, antistatic agents, nucleating agents, slip agents, plasticizers, lubricants, viscosity modifiers, tackifiers, antiblocking agents, surfactants, extender oils, acid scavengers, and metal deactivators. Additives may be used in amounts ranging from 0.01% by weight or less to 10% by weight or more, based on the weight of the layer.
[0052] Filler Examples of fillers include, but are not limited to, talc, clay, precipitated silica and silicates, fumed silica, calcium carbonate, pulverized minerals, carbon black having an arithmetic mean particle size greater than 10 nanometers, and various known flame retardants, particularly halogen-free flame retardants. Fillers can be used in amounts ranging from more than 0 to 50% by weight or more, based on the weight of the layer or the entire composition.
[0053] The olefin block copolymers and / or ethylene / α-olefin random copolymers in the upper skin layer and / or foam layer may or may not be crosslinked by specific techniques such as E-beam curing, UV curing, peroxide curing, or silane curing.
[0054] Molding and Lamination The present invention can be manufactured using the same conventional compression molding (or calendering) and lamination processes or extrusion and lamination processes used for PVC leather.
[0055] The multilayer structure may include a lower fabric layer and an upper skin layer, the latter of which is optionally coated with a top coating. The upper skin layer is manufactured by compression molding and then laminated onto the lower fabric layer. An optional PU top coating layer is then applied to the upper skin layer of the multilayer structure.
[0056] The multilayer structure may include a lower fabric layer, an intermediate foam layer, and an upper skin layer, the latter of which is optionally coated with a primer, the primer having a top coating. The upper skin layer and intermediate foam layer of the artificial leather are produced by compression molding and then laminated to each other and to the lower fabric layer in any convenient order. Foaming is typically carried out after lamination for 60 to 180 seconds in an oven typically maintained at 220°C or above. An optional primer and PU top coating layer are then applied to the laminated three-layer upper skin layer. [Examples]
[0057] Next, some embodiments of the present invention will be described in the following examples. Here, all parts and percentages are given by weight unless otherwise specified.
[0058] The raw materials used in the examples are listed in Table 1 below.
[0059] [Table 1]
[0060] Brabender mixed POE resin (37 grams) and a 0.185 g carbon black masterbatch containing 50% carbon black were mixed in a Brabender® sealed mixer at 130°C and 50 rpm for 5 minutes. The compound was recovered and used for subsequent leather preparation.
[0061] Compression molding and lamination Compounds from a Brabender® sealed mixer were compressed into a film using a 15cm × 15cm × 0.3 (or 0.5) mm mold. The POE compound from the Brabender mixture was sandwiched between PTFE film. The compound was preheated at 135°C for 3 minutes, then degassed (compression and release at 10 MPa repeated 6 times), followed by further degassing at a pressure of 10 MPa and a temperature of 135°C for 2 minutes.
[0062] After cooling, remove the top PTFE film and the fabric (woven fabric, 0.90mm thick, 300g / m²) 2 The POE film surface was coated with PTFE. After reheating for 5 minutes, it was pressed with a roller to enhance adhesion between the molten POE film and the fabric. After complete cooling, the lower PTFE film was similarly removed, and the original leather sample (with the fabric and POE layer) was recovered for subsequent coating.
[0063] Application of PU top coating The surface of the POE layer was first treated with corona to increase its surface energy (Equipment details: Nanjing Suman Electronics Co., Ltd; PLASMA GENERATOR (High-performance computerized plasma and corona discharge experimental generator)). The voltage was set to 180V and the current to 1.8A. The corona brush was moved rapidly four times over the POE layer to confirm that a high surface energy (approximately 42 dyn / cm) could be achieved.
[0064] After corona treatment, a PU top coating (95% PUD coating (Stahl's Permute WF-77-307 P77062) + 5% curing agent (Stahl's aliphatic polyisocyanate, PERMUTEX® XR-48-920, stirred for 5 minutes to mix) was spread onto the POE layer using a wire rod. The coated sample was rapidly transferred to a 130°C oven for 2 minutes for drying and curing. The resulting top coating thickness was approximately 10 μm.
[0065] Embossed finish A 15cm x 15cm leather sample was first heated at 150°C for 1 minute. The heated sample was quickly placed on an embossing mold so that the POE layer was in contact with the mold surface at a temperature of 38°C. Vacuum was applied for 10 seconds to emboss the grain on the mold onto the leather surface. The leather was then placed on a workbench with the POE layer facing the air and allowed to cool to fix the surface grain. After complete cooling and stabilization, the surface grain was observed with the naked eye under the same lighting conditions, and images were taken for comparison.
[0066] Testing and Measurement Flexibility Test The tests were conducted in accordance with ISO 17235-2002. The diameter of the metal ring was 25 mm. Three tests were performed on the leather sample, and the average of the three values was reported as flexibility. A higher value indicates greater flexibility. The flexibility tester, model GT-303, was manufactured by GOTECH TESTING MACHINES CO., LTD.
[0067] Surface texture retention measurement Differences in surface texture between different samples can be observed with the naked eye under the same lighting conditions. Generally, the thickness of the POE layer should be at least 0.1 mm, and more preferably greater than 0.2 mm, since the groove depth of the surface texture is typically less than 0.1 mm. Therefore, to cover a typical range of thicknesses, samples with thicknesses of 0.3 mm and 0.5 mm were prepared. More quantitatively, photographs of the embossed leather surface were taken under the same conditions (fixed distance of 30 cm from the sample to the camera lens, magnification of 1x, sample lighting conditions) for image analysis. 2.0 cm 2 The raised fragments separated by internal grooves (as shown in Figure 1, the surface grain consists of raised and grooved areas, and island-like raised areas are surrounded by grooves) were counted for different embodiments at the same magnification (2x) of the image. 2.0 cm of the leather surface 2 Based on the number of raised areas, the surface texture was graded as shown in Table 2.
[0068] [Table 2]
[0069] The higher the surface grading value, the better the surface texture retention.
[0070] Examples and Discussion Tables 3 and 4 below show the configuration and performance parameters of comparative examples and embodiments of the present invention.
[0071] [Table 3]
[0072] [Table 4]
[0073] As shown in Table 3, IE1 exhibited significantly better surface texture retention than CE1 (for both 0.3 mm and 0.5 mm thick POE layers) and possessed comparable flexibility. IE2 exhibited better surface texture retention than CE2. Furthermore, IE2 possessed greater flexibility than CE2.
[0074] CE3 uses the much harder random POE ENGAGE™ 8003, which resulted in improved surface texture retention. This suggests that increasing the density of random POE is beneficial. However, the trade-off is a significantly reduced flexibility (a fairly low flexibility value of 3.3). This result indicates that random POE cannot simultaneously provide good surface texture retention and high flexibility (good feel).
[0075] The CE4 and IE3 results demonstrated that blending a specific amount of OBC with random POE can help achieve both good surface texture retention and high flexibility simultaneously.
Claims
1. Artificial leather comprising a multilayer structure including an upper skin layer and a lower fabric layer, wherein the upper skin layer contains at least 10% by weight of an olefin block copolymer based on the total weight of the upper skin layer.
2. The artificial leather according to claim 1, wherein the upper skin layer comprises at least 40% by weight of an olefin block copolymer based on the total weight of the upper skin layer.
3. The artificial leather according to claim 1, wherein the upper skin layer comprises at least 50% by weight of an olefin block copolymer based on the total weight of the upper skin layer.
4. The artificial leather according to claim 1, wherein the multilayer structure further includes a foam layer between the upper skin layer and the lower fabric layer.
5. The artificial leather according to claim 1, wherein the lower fabric layer comprises a flexible polymer material.
6. The artificial leather according to claim 1, wherein the olefin block copolymer has a density of about 0.850 g / cc to about 0.890 g / cc.
7. The artificial leather according to claim 1, wherein the olefin block copolymer has an MI of about 30 g / 10 min or less at 190°C / 2.16 kg.
8. The artificial leather according to claim 1, wherein the olefin block copolymer has a melting point of 100 to 130°C.
9. The artificial leather according to claim 4, wherein the foam layer comprises at least one of (i) an olefin block copolymer and (ii) an ethylene / α-olefin random copolymer.
10. The artificial leather according to claim 1, wherein the upper skin layer substantially does not contain propylene / α-olefin copolymer.
11. The artificial leather according to claim 1, wherein the olefin block copolymer consists only of (i) ethylene and (ii) C4-C8α-olefin.
12. The artificial leather according to claim 1, wherein the artificial leather has five or more surface grain grades (POE layer with a thickness of 0.3 mm).
13. The artificial leather according to claim 1, wherein the artificial leather has four or more flexibility grades (POE layer with a thickness of 0.3 mm).
14. A method for preparing artificial leather having a multilayer structure according to any one of claims 1 to 13, The method involves preparing an upper skin layer and a lower fabric layer, wherein the upper skin layer contains at least 20% by weight of an olefin block copolymer. A method comprising laminating the upper skin layer and the lower fabric layer together.